An early archaeological example of tattooing from northwestern Alaska / Fieldiana, Anthropology, v. 66, no.1 - VanStone, James W.; Lucier, Charles V. ([Chicago] : Field Museum of Natural History, 1974)
Includes bibliographical references (p. 8-9). Fieldiana series has been published as Anthropological Series by Field Columbian Museum (1895-1909) and Field Museum of Natural History (1909-1943), and as Fieldiana: Anthropology by Chicago Natural History Museum (1945-1966) and Field Museum of Natural History (1966-).